Pendampingan Kelompok Sadar Wisata melalui Pemanfaatan Website sebagai Media Promosi Digital Desa Aik Dewa - L M Samsu; B Nadila Nuzululnisa; Hariman Bahtiar; Almi Yulistia Alwanda (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
Aikdewa Village is one of the villages that has considerable potential in natural tourism, local culture, and micro, small, and medium enterprises (MSMEs). However, these potentials have not been optimally promoted due to the lack of digital-based information media. Therefore, the development of the Aik Dewa Village Tourism Website was carried out as a digital information and promotion medium that can be accessed by the wider community. This activity aims to provide a centralized source of information related to the village profile, tourist destinations, cultural traditions, and local MSMEs products of Aik Dewa Village. The methods used in this program include field observation, data collection, system requirements analysis, interface design, website implementation, and functional testing. The developed website is designed with a simple layout and clear navigation to ensure ease of use and accessibility for users. The implementation results show that the website functions properly and is able to present village information in a structured and user-friendly manner. The existence of the Aik Dewa Village Tourism Website is expected to assist the village government and local community in promoting village potential more widely and to support the development of digital-based rural tourism